The Fallacy of No-Claim Bonus & Sustainable Crop Insurance Model for Developing World, A Success Story in Punjab-Pakistan - ABBAS, DR. MIRZA WASEEM; KHAN, DR. ABDUL QAYYUM (The journal of contemporary issues in business and government, 2021)
Attaining food security and zero hunger under the UN’s Sustainable Development Goals (SDGs) by 2030 are challenging tasks since more than 730.0 million of the world’s population earn less than 2 a day according to the World Bank report in 2018. The success of achieving these stated goals largely depends on the uplifting of small and subsistence farmers as 90% of the cultivated land for food is owned by these farmers across the world. Safeguarding farmers from the vagaries of nature, crop insurance is one of the effective risk management tools for the agriculture sector. However, for developing countries, affordable crop insurance is a challenging task because of their dilapidated economic outlook and at the same time providing premium subsidy is also essential. In this context, the developing economies have to find out some innovative solutions to cater to this challenge. The Government of Punjab-Pakistan initiated a crop insurance program in Punjab during 2017-18 by providing a 100% premium in the form of subsidy for small farmers (having less than 5 acres of landholding) to provide compensation against their yield losses due to climate change and other uncontrollable factors. The burden of the premium subsidy was immense and the Department of Agriculture Punjab introduce the concept of No Claim Bonus (NCB) or profit- sharing arrangements with insurance companies in Pakistan. The concept was implemented in 2020 through a competitive bidding process and it is a success story for Pakistan that under the NCB, part of the premium subsidy is returned back to the Government by the insurance company after deducting claims and administrative expenses. Developing countries can also experiment the crop insurance based on NCB as per their local circumstances and applicable rules.